Philosophical Consideration of Suffering and Human Resources Management in Companies - Gismera Tierno, Eduardo; Fernández Fernández, José Luis; Labrador Fernández, Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Since the dawn of human existence, suffering, as an anthropological constant, has become one of the fundamental concerns of men. Continuous attention has been paid to it, which, however, should not suppose an obstacle for us to continue doing so. Philosophy can contribute to shed light on this concept in our days, insofar as the problem of suffering, despite having received very different responses at different times of human thinking, seems to persist. The present work seeks to approach the concept of suffering from the light provided by some of the most relevant philosophical paradigms, in order to identify some practical applications in order to facilitate more adequate human resource management, both from an ethical point of view and from the business profitability side. We therefore offer proposals for responsible, sustainable and efficient human resource management, hand in hand with philosophical thought.